2015
DOI: 10.1074/jbc.m115.677245
|View full text |Cite
|
Sign up to set email alerts
|

WNT10B Enhances Proliferation through β-Catenin and RAC1 GTPase in Human Corneal Endothelial Cells

Abstract: Background: Adult human corneal endothelial cells are G 1 -arrested, often necessitating transplantation in patients with endothelial dysfunction. Results: WNT10B enhances proliferation in human corneal endothelial cells. Conclusion: Modulation of the WNT10B pathway could be used to treat vision loss because of corneal endothelial dysfunction. Significance: Modulation of the WNT10B pathway may provide a means of addressing the impending increase in donor cornea demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 66 publications
3
23
0
Order By: Relevance
“…We have previously reported that cell migration and proliferation are independently regulated by WNT5A and WNT10B respectively in human corneal endothelial cells (43,44). In this study, we investigated the downstream targets of FGF2 that regulate cell proliferation and fibrosis in primary human CEC and human ex vivo corneal endothelium.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We have previously reported that cell migration and proliferation are independently regulated by WNT5A and WNT10B respectively in human corneal endothelial cells (43,44). In this study, we investigated the downstream targets of FGF2 that regulate cell proliferation and fibrosis in primary human CEC and human ex vivo corneal endothelium.…”
Section: Discussionmentioning
confidence: 97%
“…Protein Preparation, Protein Assay, SDS PAGE, and Immunoblotting Analysis -All assays were performed following previously reported protocols (12, 40,43,44). The following gel concentrations were used to separate proteins: 15% polyacrylamide gel for SNAI1 and SNAI2, 12% polyacrylamide gel for CDK2, 10% polyacrylamide gel for COL8A2, cyclin E1, vimentin, cytokeratin 12, αSMA, and β-actin, 8% polyacrylamide gel for E-cadherin, type I collagen, ZEB1 and ZEB2, and 6% polyacrylamide gel for Fibronectin.…”
Section: Methodsmentioning
confidence: 99%
“…The Wnt signaling pathway is gaining prominence as an underappreciated player during inflammatory disorders such as atherosclerosis. In vitro, Wnt ligands have been shown to induce EC proliferation and modulate inflammation (24)(25)(26). Noncanonical Wnt5a/Ca 2+ -dependent signaling induces endothelial inflammation and release of inflammatory cytokines (27).…”
Section: Discussionmentioning
confidence: 99%
“…Canonical Wnt proteins, namely, Wnt1, Wnt3a, Wnt7a, Wnt7b, and Wnt10b, have been demonstrated to activate ␤-catenin signaling in endothelial cells (ECs) and to regulate target genes that affect the angiogenic process (3)(4)(5)(6). In addition to its essential structural role in cadherin-based adhesions, ␤-catenin is a regulator of Wnt-mediated gene expression through its association in the nucleus with the T-cell factor/lymphoid-enhancing factor (TCF/LEF) (7)(8)(9).…”
mentioning
confidence: 99%
“…In the absence of Wnt stimulation, free cytoplasmic ␤-catenin levels are kept low by a degradation complex that includes glycogen synthase kinase 3␤ (GSK3␤), adenomatous polyposis coli (APC), and axin (10)(11)(12). Upon Wnt stimulation, ␤-catenin is stabilized in the cytoplasm and subsequently translocalized to the nucleus, interacts with TCF/LEF, and enhances the expression of genes involved in cell proliferation, differentiation, cell fate, and survival (6,(13)(14)(15).…”
mentioning
confidence: 99%